Outbreak of recurrent abdominal cramps associated with Arcobacter butzleri in an Italian school. - Vandamme, P (1992)
In the autumn of 1983, an outbreak of recurrent abdominal cramps occurred in a nursery and primary school in the Rovigo area in Italy. None of the 10 affected children had diarrhea. An atypical Campylobacter-like organism was isolated from feces in all cases. Conventional enteropathogens were searched for but not detected. The Campylobacter-like organism was identified as Arcobacter butzleri by using sodium dodecyl sulfate-polyacrylamide gel electrophoresis of whole-cell proteins and cellular fatty acid analysis. Its identity was confirmed by DNA-DNA hybridizations versus Arcobacter reference strains. All of the preserved outbreak strains have identical protein profiles and phenotypic characteristics and belong to serogroup 1 of the Lior serotyping scheme on the basis of slide agglutination of crude and absorbed antisera of A. butzleri reference strains versus heat-labile antigens of live bacteria. These data point to an epidemiological relationship. The successive timing of the cases suggests person-to-person transmission.